1998
DOI: 10.1002/mds.870130328
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary palatal tremor in two siblings

Abstract: We report two siblings with palatal tremor (PT) and ear clicks who can voluntarily elicit or suppress both PT and ear clicks by just "thinking" about starting or stopping the sounds. The patients were also able to voluntarily modulate the frequency of their ear clicks and PT. They did not have any signs of cerebellar, brain stem, or other neurologic disease. These familial palatal movements may represent a variant of palatal tremor but can not satisfactorily be classified as either symptomatic or essential PT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 16 publications
3
27
0
Order By: Relevance
“…A) at rest: tremor bursts involve the genioglossal (traces 1,3,5,7) but not the digastric muscle (traces 2,4,6,8); B) active jaw opening: during the task sustained voluntary tonic activation of the digastric muscle is associated with tremor bursts stop in the genioglossal muscle (black arrows), which reappear after jaw closure (dotted arrows); C) passive jaw opening: between two brief voluntary phasic muscle contractions of the digastric muscle (arrows), necessary to allow insertion and removal of a small object to bite, muscle relaxation replaces tremor bursts in the genioglossal muscle. In each panel time base is 200 ms/div (each horizontal trace 4s); sensitivity 500 µV/div It has been reported that EPT can be modified by different manoeuvres including mental processing [2,11,15,22,25], neck position [23], speaking [4,11], singing [4] or mouth opening [2,25]. The findings observed in our patients confirm that mouth opening and other situations that imply mouth opening may completely suppress PT.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A) at rest: tremor bursts involve the genioglossal (traces 1,3,5,7) but not the digastric muscle (traces 2,4,6,8); B) active jaw opening: during the task sustained voluntary tonic activation of the digastric muscle is associated with tremor bursts stop in the genioglossal muscle (black arrows), which reappear after jaw closure (dotted arrows); C) passive jaw opening: between two brief voluntary phasic muscle contractions of the digastric muscle (arrows), necessary to allow insertion and removal of a small object to bite, muscle relaxation replaces tremor bursts in the genioglossal muscle. In each panel time base is 200 ms/div (each horizontal trace 4s); sensitivity 500 µV/div It has been reported that EPT can be modified by different manoeuvres including mental processing [2,11,15,22,25], neck position [23], speaking [4,11], singing [4] or mouth opening [2,25]. The findings observed in our patients confirm that mouth opening and other situations that imply mouth opening may completely suppress PT.…”
Section: Discussionsupporting
confidence: 92%
“…In fact, even though many uncertainties still exist about the pathophysiology of both EPT and SPT, some evidence suggests a cortical influence on the generator of PT. Indeed, PT may be voluntarily influenced by simply concentrating on it [11,15,22], without performing any movement. In addition, transcranial magnetic stimulation of the motor cortex may modulate PT [1].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is now clear that certain clinical features that might be thought to be either impossible to be performed voluntarily or specific for an alternate neurological disorder may be seen in psychogenic disorder. Thus, Munhoz et al [10 ] reported that the geste antagoniste, one of the characteristic features of idiopathic torsion dystonia, can be seen in psychogenic dystonia, and palatal tremor has been reported both in the context of a psychogenic disorder [11 ], and with its frequency under voluntary control [12]. Furthermore, dyskinesias following intravenous apomorphine abuse have been observed in a patient with psychogenic parkinsonism despite intact striatal dopamine metabolism [13 ].…”
Section: Diagnosismentioning
confidence: 96%
“…However, our patient was able to voluntarily induce or stop the tremor. Even if voluntary modulation of palatal tremor has been reported in literature in some cases of essential palatal tremor, our patient has developed possible voluntary control, suggesting the acquisition of special motor skills rather than an inhibition of involuntary movements, and this seems suggestive of a psychogenic etiology 16. Limited data are available about psychogenic movement disorders in children, but clinical findings suggesting a psychogenic cause similar to that in adults, including inconsistent character of the movements, exacerbation with stress and while paying attention, and disappearance when distracted, as well as a response to placebo and improvement with psychotherapy.…”
Section: Discussionmentioning
confidence: 49%